A Case Report of Majocchi's Granuloma Associated with Combined Therapy of Topical Steroids and Adalimumab. Issue 2 (January 2016) - Chou, Wan-Yi; Hsu, Chih-Jung
Abstract : Abstract: Currently, tumor necrosis factor alpha (TNF-alpha) inhibitors are widely used for many autoimmune disorders. However, they cause an immunocompromised status that sometimes leads to many cutaneous side effects including atypical infections. Herein, we report the first case of adalimumab-related Majocchi's granuloma. A 43-year-old Taiwanese male patient with chronic plaque-type psoriasis developed numerous tender nodules 1 month after adalimumab injection. The nodules responded poorly to bacterial folliculitis treatment. After repeated skin biopsies for pathology and tissue fungal culture, Majocchi's granuloma was confirmed. Adalimumab was withheld, and 12 weeks of terbinafine treatment was given. On completion of treatment, the nodular skin lesions and dystrophic nail lesions improved dramatically. The information, including time span, clinical features, histological findings, and improvement following withdrawal of adalimumab and treatment with an oral antifungal agent, indicates that Majocchi's granuloma was adalimumab-related. Psoriasis patients are more susceptible to dermatophyte infection due to local and systemic immunosuppressant therapy. It is important to perform a thorough examination for latent dermatophyte infection, including skin and nail lesions, before treatment with TNF-alpha inhibitors and during traditional psoriasis treatment. When atypical presentation together with treatment failure is noted in psoriasis patients prescribed biologics, clinicians should investigate evidence of dermatophyte infection and provide proper treatment. Sometimes, multiple skin biopsies and tissue fungal cultures are required to establish a correct diagnosis.